Mechanical and Chemical Mechanical Planarization of Single-Crystal Diamond (100) Substrate - Kubota Akihisa (International journal of automation technology, 2025)
A sequential polishing method for single-crystal diamond substrates under atmospheric conditions is demonstrated. The process consists of two stages: (1) rough polishing using mechanical polishing with 3 µm diamond abrasives and (2) finish polishing through chemical mechanical planarization employing a nickel plate with hydrogen peroxide (H2O2) solution as the oxidizer. Each stage of the diamond (100) polishing process was conducted for 1 h. Surface flatness and microroughness were evaluated using a scanning white light interferometric microscopy and atomic force microscopy, while subsurface damage was examined by high-resolution transmission electron microscopy. Experimental results show significant improvements: the surface flatness of the diamond substrate was enhanced, and the surface roughness was reduced from Sa=3.667 nm to Sa=0.120 nm after 2 h of polishing. In addition, power spectral density analysis confirmed a reduction in surface roughness within the spatial wavelength range of 10–1000 µm following finish polishing. The subsurface damage depth after finish polishing was found to be less than 1 nm. These findings demonstrate that the proposed two-step polishing method effectively produces high-precision diamond surfaces with high efficiency.